Life cycle meta-analysis of carbon capture pathways in power plants: Implications for bioenergy with carbon capture and storage. (October 2021) - Bennett, Jeffrey A.; Abotalib, Mohammad; Zhao, Fu; Clarens, Andres F.
Highlights: Existing power plants can be retrofitted for bioenergy with carbon capture (BECCS). IGCC plants have highest energy return on investment, lowest water use. Steam cycle plants are more abundant and smaller, compatible with bioenergy. Steam cycle plants have competitive performance when cofiring coal and biomass. Calcium-looping and membrane capture technologies optimal for co-fired steam cycles. Abstract: Bioenergy with carbon capture and storage (BECCS) based electricity generation is one possible approach for delivering large-scale carbon dioxide removal from the atmosphere. This study evaluates the environmental impacts of leveraging existing power plants for BECCS. We performed a life cycle meta-analysis of eight carbon capture technologies, including five previously simulated only for coal and natural gas, for both steam cycle and integrated gasification combined cycle (IGCC) power plants. We found that IGCC plants offer the best balance of negative emissions, energy return on investment (EROI) and low water use irrespective of capture technologies. Planned IGCC plants tend to be large whereas biomass-fired power plants are often small and distributed in the landscape because of the distributed nature of the fuel. Steam cycle plants had larger negative emissions, but also lower EROI, and so blending with coal may be necessary to achieve a suitable EROI. Steam cycles were sensitive to capture technology type, and results found membrane and calcium looping capture technologies offer a balance between negative emissions, EROI and water use when fired using coal-biomass blends. These results suggest that steam cycle power plants may be the most desirable candidates to support early-stage deployment of BECCS.